Relationships between diets and the quality of life to women aged 50 to 64 - Ewa Stępień; Joanna Baj-Korpak; Krystyna Gawlik; Barbara Bergier; Agata Pocztarska; Mirosława Sidor; Adam Szepeluk (National Institute of Public Health - National Institute of Hygiene, 2019)
Background. Adverse effects of numerous environmental factors, including improperly balanced diets, may accelerate the onset of ailments related to the climacteric period. Objective. The aim of the study was to examine the relationships between diets and the quality of life of working women aged 50-64 years. Material and methods.The study included 274 working women aged 55.4±4.0 years living in Biała Podlaska and the surrounding area. These were women working in various positions (teaching, administrative, economic department) at the State School of Higher Education in Biała Podlaska, Poland and patients of the Health and Rehabilitation Centre in Biała Podlaska. The study was conducted by means of a popular tool used to diagnose quality of life i.e. SF-36 questionnaire (Short Form Health Survey) and the Questionnaire of Eating Behaviour (QEB). Results. In all categories of quality of life (SF-36), apart from pain and general health, there were statistically significant differences between the results of the respondents and the norm for Polish women aged 50 to 60 years. Fruit, vegetables and wholemeal bread were the most frequently consumed products in the healthy diet group, while legumes, fish and curd cheese were the least frequently consumed by the respondents. Of the unhealthy products, the women most often chose sweets (at least once a week), cheese and fried food. Analysis of the effect of a healthy diet on the quality of life showed that a statistically significant correlations were observed in the case of mental health, functioning in society, emotionality, vitality, and well-being. Conclusions. A positive correlation with the application of a healthy diet was observed in all the categories of quality of life. This means that the respondents with healthy diets had a higher quality of life.